A review of methods for quantifying contribution of vehicular emission to fine particulatematter (in Chinese) - CQ Yan; M* Zheng (Chinese Sci. Bull., 2017)
China is facing serious haze problems due to the levels of fine particulate matter (PM2.5). Therefore, source apportionment of PM2.5 is required for formulating effective air pollution control strategies. The fast increase of the vehicle population, especially in the megacities of China in recent years, makes vehicular emissions one of the most important sources of PM2.5 and has led to it receiving great attention and concern. There is an urgent need to accurately and quantitatively estimate the contribution of vehicular emissions. A growing number of studies have been conducted for source apportionment of PM2.5 in China and report the contribution from vehicular emissions using different methods. However, it is still a big challenge as to how vehicular emissions can be accurately quantified. This study summarizes the various methods that have been used to identify and quantify the vehicular emissions contribution to PM2.5 in published literature by international and domestic scientists, lists advantages and disadvantages of each method, and proposes ways to reduce its uncertainty. In general, methods for estimating vehicular emission contributions in previous studies include emission inventory based methods, chemical transport models, receptor models, hybrid models etc. The receptor model based method is the most commonly applied method in China. Source profiles of vehicular emissions based on source testing in China, and organic and inorganic tracers used for diagnosing vehicular emissions, which are two key factors for quantifying vehicular exhaust in receptor models, are also summarized here. Contributions of vehicular emissions to ambient PM2.5 reported in different areas in China, especially Beijing, are listed and compared. It can be seen that the contribution of vehicular emissions to PM2.5 varies significantly with the study area, year of the study, as well as the methods in use. The vehicular emissions contribution to PM2.5 in Beijing is reported to be in the range of 4%–36% based on previous studies from 1989 to 2014, primarily using the receptor model method. This work also points out challenges in the current studies, provides suggestions in order to better quantify the contribution from vehicular emissions in China, and proposes ways to optimize the methods. For example, besides primary emissions from vehicular exhaust, quantifying secondary organic and inorganic aerosols formed from gaseous and particulate precursors from vehicular emissions, as well as traffic related sources (e. g., resuspended road dust) is also a big concern and challenge for accurately estimating vehicular emissions. In addition, there is still a pressing need to develop more detailed and comprehensive chemical profiles and an emissions inventory of vehicular emissions, with standardized sampling and analytical protocols in the future. An improved emission inventory with high time, spatial and species resolutions should be established. A hybrid model, which integrates emission inventory, chemical transport model, receptor model and observational data is a promising direction to provide an accurate estimate of vehicular emissions in the future. In addition, there is a need to develop a system to verify the results obtained from a source apportionment study.